The image of the global citizen model in the education system based on the views of contemporary philosophers - Rouia Bouiri; Abass Ghateltash; Sayed Ahmad Hashemi; Aliasghar Mashinchi (هنر اسلامی, 2022)
Due to increasing cultural diversity around the world, in this century, citizens need knowledge, attitudes and skills to function in their own cultural communities as well as beyond their cultural boundaries. The purpose of this study is to provide a model of educational ideals of free citizens of the world based on the views of contemporary education philosophers. For this purpose, descriptive-analytical research method and confirmatory explanatory approach were used and data were collected from the book of ideas of contemporary philosophers related to the field of global citizenship. Different categories around the subject were obtained in the form of a paradigm model including: causal conditions (necessity, needs); Central category (content); Strategies (teacher role, learning methods, evaluation); Background (time, space, accordance with the conceptual model and the qualitative findings of the research indicate free global citizens in The shadow of vocational education can train an informed, committed and skilled workforce for the knowledge community and knowledge management in response to the third millennium.Research purposes1- Identifying the dimensions of the idea of realizing the educational ideal of the citizens of the world from the perspective of philosophers of contemporary education,2- Analysis of components, contexts and critical approaches regarding the desired modelResearch questions1- How to identify the dimensions of the idea of realizing the educational ideal of the citizens of the world from the perspective of contemporary philosophers of education?2- How to analyze the components, contexts and critical approaches regarding the desired model?